Spontaneous Mutations That Confer Antibiotic Resistance in Helicobacter pylori - Wang, Ge (American Society for Microbiology, 2001)
In this study, we systematically examined in vitro frequencies and spectra of the spontaneous mutations in Helicobacter pylori that confer resistance to clarithromycin (Cla(r)), metronidazole (Mtz(r)), amoxicillin (Amx(r)), ciprofloxacin (Cip(r)), and rifampin (Rif(r)). The mutation rate of Rif(r) or Cip(r) determined in a fluctuation assay is 1 × 10(−8) to 2 × 10(−8) per cell per division. In contrast, the mutation rates of Cla(r), Mtz(r), and Amx(r) are much lower (<10(−9)). However, Mtz(r) mutants could be readily selected in vitro by using the serial passage method, suggesting that the mutagenic effect and selective effect of a sublethal dose of metronidazole contribute to the rapid development of Mtz(r). Analysis of spontaneous Rif(r), Cla(r), and Cip(r) mutants confirmed previous results indicating that mutations within the rpoB gene, the 23S rRNA gene, and the gyrA gene, respectively, are responsible; also, several new mutant alleles were identified. Mtz(r) mutants resulted most frequently, but not always, from mutations in the rdxA gene. DNA fragments containing each mutant allele could readily transform susceptible H. pylori strains to resistance, confirming that each mutant allele is responsible for the resistance phenotype.